Species description of Rhizophoraceae family in mangrove forest at Baluran Nasional Park East Java - SUDARMADJI SUDARMADJI (Society for Indonesian Biodiversity, 2004)
Research about species description of Rhizophoraceae family in mangrove forest at Baluran National Park was conducted from June to October 2003. The method were plot and survey. There were nine species of Rhizophoraceae. The species at mangrove were Bruguiera cylindrica, B. gymnorrhiza, B. sexangula, Ceriops decandra, C. tagal, Rhizophora apiculata, R. lamarckii, R. mucronata, and R. stylosa. In addition, the number species of Rhizophoraceae family in the mangrove forest at Baluran National Park were more completely than another places, because it was found more than 75 percent species of Rhizophoraceae.Â© 2004 Jurusan Biologi FMIPA UNS SurakartaKey words: Rhizophoraceae, mangrove forest, Baluran National Park.